The role of sponsorship marketing in the integrated marketing communication programme with reference to the German insurance company Cosmos Direkt - Jantzen, Elke Simone (Stellenbosch : Stellenbosch University, 2012)
Assignment (MComm)--University of Stellenbosch, 2002.